Without spirometry, how accurate is the diagnosis of COPD?. Issue 9 (September 2015) - Blanchard, Terin; Savel, Paul
Abstract : Evidence‐Based Answer : Smoking history, a previous history of respiratory disease, abnormal breath sounds on examination, and a prolonged expiratory time may help in the diagnosis of chronic obstructive pulmonary disease (COPD); overall clinical impression is 83% sensitive. However, using clinical history and examination alone would still miss many patients with COPD on spirometry (SOR: B, based on systematic review and cross‐sectional trials).